Aspectos sociológicos da venda direta no setor de produtos de higiene pessoal, perfumaria e cosméticos :uma análise a partir de narrativas biográficas - Ugalde, Marise Mainieri de (2015)
Direct sales have been an important distribution channel for the commercialization of consumer goods, particularly in the sector of cosmetics, toiletries and fragrance, which has been reaching a substantial increase in sales in the last few years, particularly in Brazil. The direct sales organizations have the capacity of attracting a huge team of autonomous sellers with whom they establish a merely commercial relationship, assuring a great territorial presence of the brand that is being sold. With the aim of understanding the sociological aspects of direct sales of cosmetics, toiletry and fragrance products, the thesis made use of the biographical narratives approach developed by the German sociologist Gabriele Rosenthal. Therefore, from the reconstruction of a single biographic case- the case of Noeli, seller of Avon and Natura brands- it was possible to access the relevance system of the narrator and apprehend the emergent meanings of her own discourse.Moreover, in order to evidence the cross-disciplinary link between Social Sciences and Administration, content analysis was used to verify how this theoretical suggestions presented at Nicole Biggart’s Charismatic Capitalism, which is considered the most important sociological study on direct sales. The results indicate that the topics that arose from the reconstruction of Noeli’s biographic case are in consonance with central topics listed by Biggart (1990), which could be grouped in three main categories: lack of distinction between private and public spheres, gender, and entrepreneurship. The topics “centrality of work” and “occupational prestige” were identified in the reconstruction of the biographic case, but they are not included among the themes studied by Biggart (1990). The academic and managerial implications have also been presented here, as well as the limitations and suggestions for new studies.